PENGARUH KOMPOSISI HERBAL DALAM MINUMAN TEH HIJAU GAMBUNG HERBAL TERHADAP HAMBATAN Î±-GLUKOSIDASE - Megawati, Megawati; Mulyani, Hani; Minarti, Minarti; Ernawati, Teni; Darmawan, Akhmad (Jurnal Ilmiah As-Syifaa, 2018)
The aim of this study is to make a formula of green tea that is enriched by other herbs. Green tea drinks are made using the basic ingredients of gambung (THG) green tea enriched with sapodilla leaves (Manilkara zapota (Aw) bay leaves (Syzygium polyanthum (Am), Artocarpus communis (Un) breadfruit leaves, and cinnamon leaves (Cinnamomum verum (K)). The composition of gambung herbal green tea is made by reference to the antidiabetic activity of each herb. All the samples were tested for inhibition of Î±-glucosidase enzymes and toxicity using the lethality test method for brine shrimp. All samples showed good inhibition of the Î±-glucosidase enzyme barriers of gamboeng green tea (THG) 82.05%, sapodilla leaves (Aw) 97.81%, breadfruit leaves (Un) 73.34%, bay leaves (Am) 93.80%, cinnamon leaves (K) 91.24 %. The inhibition value of Î±-glucoside enzymes in the formulation of gamboeng herbal green tea drinks: 96.203% (GKUn) is higher when compared to the GKAm formula (94.78%) and GKAw (62.487%).